DOP029 Treatment and long-term outcomes of paediatric patients with penetrating Crohn's disease. (16th January 2018) - Kollen, L; Leroyer, A; Breton, A; Fumery, M; Savoye, G; Lemale, J; Morin, D; Pariente, B; Mas, E; Turck, D; Al Khouri, M; Blanc, P; et al.
Abstract: Background: Penetrating phenotype and young age at diagnosis are two risk factors of complicated course in Crohn's disease (CD). Currently, only few data are available regarding the treatment and the evolution of penetrating CD in children. The aim of our study was to describe the clinical management and to evaluate the long-term outcomes of children with penetrating CD. Methods: We performed a retrospective multicentre study in two French tertiary referral centres and one population-based registry (EPIMAD) including CD paediatric patients with a luminal penetrating phenotype (B3) diagnosed before the age of 18 year-old between 1995 and 2016. Isolated perianal CD were excluded. Demographic characteristics, type of B3 (abscess or fistula), initial treatment (medical, drainage or intestinal resection in the first 3 months), treatments during follow-up and long-term outcomes were collected. Complicated outcome was defined as penetrating phenotype recurrence or intestinal resection during the follow-up. Results: Eighty-four patients (51 males, 33 females) with CD and a mean age of 15.1 ± 2.4 year-old at B3 diagnosis were included with a median follow-up of 10.5 (IQR: 5.0–14.6) years. B3 phenotype revealed the CD diagnosis in 30% of the cases. At B3 diagnosis, 60% (50/84) of the patients had an intra-abdominal abscess, 15% (13/84) a complex fistula and 25% (21/84) a simple fistula (only one fistula tract with no involvement of other organs). In 36% (39/84) of the cases an intestinal stricture was associated to B3. For initial B3 management, 80% (61/76) of the patients received antibiotics, 41% (30/74) enteral nutrition, and 26% (19/72) parenteral nutrition. No children had a radiologic drainage and 12% (10/84) had a surgical drainage. Half of the patients (42/84) had an early intestinal resection for B3 treatment. Among patients without early surgery, 36% (15/42) received a thiopurine and 26% (11/42) an anti-TNFα agent in the first 3 months after B3 diagnosis. During follow-up, 30% (25/84) of patients had a B3 recurrence with a median delay of 37.6 (20.0–74.0) months and 27% (23/84) had an intestinal resection for CD with a medina delay of 83.4 (43.4–141.5) months. Early intestinal resection for B3 was significantly associated with a decreased risk of B3 recurrence (HR = 0.23; IC 95% [0.07–0.63]) and intestinal resection (HR = 0.23; IC 95% [0.07–0.59]) during follow-up. Indeed, only 12% (5/42) of the patients with an early intestinal resection had a B3 recurrence compared with 48% (20/42) of the patent without early surgery. Conclusions: Half of the children with penetrating CD had an early intestinal resection for B3 treatment. This early surgery significantly decreased the risk of B3 recurrence and intestinal resection during follow-up.